Analisis Efek Globalisasi Terhadap Perdagangan Internasional Negara Indonesia - Feronica Simanjorang; Kristianti Putri; Chairul azmi puteh; Elsya Vidara Sirait; Jeslyn Lie; Dio Rabintar (Universitas Katolik Widya Karya Malang, 2023)
At this time, international trade has become an important part of business development. This is demonstrated by the development of multinational companies. International trade is the exchange of products between countries. This entails buying and selling of products between other countries, as well as transactions between people from different countries. This research data collection approach is a secondary data collection technique. Data collection in research research was carried out by means of a literature study. Data analysis in this study used descriptive analysis, namely by describing the data qualitatively in the form of sentences and statements to make it easier to read and understand the data. Based on the results of the research, it was found that the main factors influencing international trade in the State of Indonesia with the current conditions are the potential of the State of Indonesia in producing or the resources it owns as well as requests from other countries. exports, foreign tourists and e-commerce which can increase the amount of national income of the State of Indonesia. In addition, the negative impact of globalization on international trade in Indonesia is an increase in the number of imports, economic inequality and acceptance of foreign culture which can reduce the amount of national income of the Indonesian state and kill local industries in Indonesia.